Assessment of health-related quality of life and health-seeking behavior in female cardiac patients in rural setting of Pakistan: A comprehensive cross-sectional analysis - Amna Zeb; Faizan Ali Razzaq; Shahbaz Ahmad Zakki; Ijaz ul Haq; Muhammad Subhan Nazar; Ussama Hafeez (Clinical Epidemiology and Global Health)
Background: This study assessed various factors related to cardiac patients, focusing on their health-related quality of life (HRQOL), health-seeking behavior, and their association with demographic variables. The aim was to explore HRQOL and health-seeking behavior in cardiac patients. Methods: The study included 403 participants aged 18–59 years. Demographic characteristics, HRQOL, and health-seeking behavior were assessed using the SF-36 V2 and HBS-16 questionnaires. Statistical analyses, including Mann-Whitney U tests and adjusted odds ratios, were performed using SPSS version 22.0 to examine the relationship between these factors and variables such as family medical history, smoking status, and demographic data. Results: The findings revealed that many cardiac patients reported low HRQOL, while 76.7 % demonstrated positive health-seeking behavior. Associations were found between HRQOL and factors like family history of cardiac disease and smoking status. Those with a family history showed different health-seeking behaviors and emotional well-being. Smokers also exhibited distinct health-seeking patterns. Demographic factors like age, occupation, marital status, family history, and smoking status influenced HRQOL and health-seeking behavior. Conclusion: This study highlights the complex relationship between cardiovascular disease, quality of life, and health-seeking behavior. Socioeconomic and lifestyle factors, such as smoking and inactivity, significantly impact HRQOL and health outcomes. Targeted interventions, including public health campaigns and early risk assessments, are essential to improve HRQOL and healthcare outcomes for cardiac patients, particularly those with limited access to care.